A Simulation Competition on Neonatal Resuscitation as a New Educational Tool for Pediatric Residents - Lorenzo Zanetto; Francesco Cavallin; Nicoletta Doglioni; Benedetta Bua; Sandro Savino; Giuseppe De Bernardo; Simone Pratesi; Paolo Ernesto Villani; Gary M. Weiner; Daniele Trevisanuto; on behalf of the Task Force on Neonatal Resuscitation of the Italian Society of Neonatology (MDPI AG, 2023)
Background: Training programs on resuscitation have been developed using simulation-based learning to build skills, strengthen cognitive strategies, and improve team performance. This is especially important for residency programs where reduced working hours and high numbers of residents can reduce the educational opportunities during the residency, with lower exposure to practical procedures and prolonged length of training. Within this context, gamification has gained popularity in teaching and learning activities. This report describes the implementation of a competition format in the context of newborn resuscitation and participants' perceptions of the educational experience. Methods: Thirty-one teams of three Italian pediatric residents participated in a 3-day simulation competition on neonatal resuscitation. The event included an introductory lecture, familiarization time, and competition time in a tournament-like structure using high-fidelity simulation stations. Each match was evaluated by experts in neonatal resuscitation and followed by a debriefing. The scenarios and debriefings of simulation station #1 were live broadcasted in the central auditorium where teams not currently competing could observe. At the end of the event, participants received an online survey regarding their perceptions of the educational experience. Results: 81/93 (87%) participants completed the survey. Training before the event mostly included reviewing protocols and textbooks. Low-fidelity manikins were the most available simulation tools at the residency programs. Overall, the participants were satisfied with the event and appreciated the live broadcast of scenarios and debriefings in the auditorium. Most participants felt that the event improved their knowledge and self-confidence and stimulated them to be more involved in high-fidelity simulations. Suggested areas of improvement included more time for familiarization and improved communication between judges and participants during the debriefing. Conclusions: Participants appreciated the simulation competition. They self-perceived the educational impact of the event and felt that it improved their knowledge and self-confidence. Our findings suggest areas of improvements for further editions and may serve as an educational model for other institutions.